Peningkatan Efisiensi Operasional Pergudangan Melalui Teknologi Canggih - Hendra Zulfikar; Dimas Rizki Saputra; Ahmad Maulana; Yohan Ananda Cahyono; Siti Sahara (Jurnal Ilmiah Wahana Pendidikan, 2023)
Efficient warehousing is a critical element in a successful supply chain. In an effort to improve the efficiency of warehousing operations, the use of advanced technology has become the focus of research and attention in the industry. The purpose of this research is to investigate how advanced technology can improve operational efficiency of warehousing. This research analyzes several advanced technologies that have been implemented in warehousing activities, including automated warehouse management systems, robotics, Internet of Things (IoT), data analytics, and artificial intelligence. Through literature reviews and case studies, the authors collect relevant data on the benefits resulting from the use of advanced technology in warehousing. The results of the study show that the use of advanced technology in warehousing has provided significant benefits. Automated warehouse management systems enable the process of receiving, storing, and shipping goods to be carried out quickly and accurately, reducing human errors and increasing productivity